2020
DOI: 10.1017/s0959269519000334
|View full text |Cite
|
Sign up to set email alerts
|

Some quantitative aspects of written and spoken French based on syntactically annotated corpora

Abstract: Based on two syntactically annotated corpora, and within the theoretical tradition of dependency grammar, the current study investigates the quantitative differences and similarities between written and spoken French. Our findings support the assumption that spoken and written French are two realizations of one language that do not differ in the syntactic categories, but in the frequency of these categories, and also in their organization in sentence. The subjects in spoken French are mostly pronouns, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Because of its strict usage, important documents such as strict laws are written in French internationally. e United Nations has designated French as the first speech language and the first written language [2].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its strict usage, important documents such as strict laws are written in French internationally. e United Nations has designated French as the first speech language and the first written language [2].…”
Section: Introductionmentioning
confidence: 99%
“…This finding showed an interaction between dependency distance and dependency types. In a more recent research, differences in the MDD of individual dependency types were also observed in spoken and written French (Poiret and Liu, 2020). Based on two treebanks, Poiret and Liu (2020) found that the MDDs of major dependency types (e.g., subject, oblique object) are greater in written French than in spoken French.…”
mentioning
confidence: 96%
“…In a more recent research, differences in the MDD of individual dependency types were also observed in spoken and written French (Poiret and Liu, 2020). Based on two treebanks, Poiret and Liu (2020) found that the MDDs of major dependency types (e.g., subject, oblique object) are greater in written French than in spoken French. As a result, further investigation into the diachronic change of dependency types is needed to examine their effects on DDM.…”
mentioning
confidence: 96%
“…Different languages [25] and genres [26] have different syntactic expressions, and the four treebanks can minimise the influence of languages and genres as much as possible. The format of treebanks is CoNLL-X [27], and the required content extracted from it can be seen in table 1.…”
mentioning
confidence: 99%